2020
DOI: 10.3390/app10207216
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Aerodynamic Performance of Savonius Wind Rotor Using Straight-Arc Curtain

Abstract: A straight and an arc-shaped curtain are combined to enhance the aerodynamic performance of the Savonius wind rotor. The straight-arc curtain is placed in front of the Savonius wind rotor to reduce the negative moment on the convex blade and increase the positive moment on the concave blade. The static and dynamic performances of the Savonius wind rotor with and without the curtain are investigated based on the computational fluid dynamics method. The results show that the static torque is higher with the curt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In particular, the conservation of mass and momentum were implemented. As a turbulence model, the SST k-ω was employed since several studies revealed its estimation capabilities in VAWTs [39][40][41][42][43]. In a previous work [44], several turbulence models were compared, and it was concluded that the SST k-ω is the most appropriate for these simulations although the computational cost was higher than other turbulence models, such as the commonly employed k-ε.…”
Section: Numerical Modelmentioning
confidence: 99%
“…In particular, the conservation of mass and momentum were implemented. As a turbulence model, the SST k-ω was employed since several studies revealed its estimation capabilities in VAWTs [39][40][41][42][43]. In a previous work [44], several turbulence models were compared, and it was concluded that the SST k-ω is the most appropriate for these simulations although the computational cost was higher than other turbulence models, such as the commonly employed k-ε.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Results showed that at the same angle of attack, static torque is higher with the curtain compared to without any curtain. Compared to the conventional rotor, a 50% gain in power coefficient with the curtain was reported (Zhang et al, 2020). Rengma investigated the interaction of twin Savonius Hydrokinetic turbines experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency can also be increased through some paramete lated to the rotor design, such as the aspect ratio (AR), overlap (O), separation gap twist angle (TA), number of blades, etc. [17][18][19]. Figure 1a illustrates a 3D view of a S nius turbine.…”
Section: Introductionmentioning
confidence: 99%